2-Aminoaryl Benzimidazoles towards Potent Antimicrobial Agents - Aravind, S.; Boddapati, S. N. Murthy; Singh, Surinderpal; Kumar, T. Kiran; Somasekhar, T.; Emmanuel, K. A.; Prasad, G. Giri (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
A series of 2-aminoarylbenzimidazoles (3a-l) compounds were screened for their in vitro antimicrobial properties. In the current work, efforts to synthesize 2-aminoarylbenzimidazole derivatives with strong antibacterial activity have been outlined. Xanthomonas campestris, Escherichia coli, Bacillus cereus, Bacillus megaterium, and a fungal strain called Candida albicans were the four microbial strains used to test the prepared compound’s antimicrobial activities. Biological evaluation studies of these 2-aminoarylbenzimidazole derivatives have demonstrated that a number of the tested compounds exhibit moderate to good in vitro antimicrobial activities. The compounds 3a, 3b, 3i, 3j, and 3l exhibited outstanding inhibitory activity. The present study offers an intriguing profile to support experimental studies, mainly in the field of antimicrobial research.